SELF-ESTEEM, SELF-CONCEPT AND SELF-IMAGE: INFLUENCES ON YOUR DEVELOPMENT PROCESS IN CHILDHOOD - dos Santos Ribeiro, Ivana; dos Santos Ribeiro, Itana; Vieira Góis dos Santos, Thaís (Health and Society, 2023)
Self-esteem corresponds to a feeling of personal worth and self-respect, considering a positive or negative evaluation of oneself, while self-concept is attributed a descriptive and evaluative character, the first being related to self-image and the second to self-esteem. In order to build healthy self-esteem, the involvement of family members and school staff is strictly necessary, in order to provide a safe and motivating environment for children and adolescents. Thus, this article has the general objective of understanding the processes of building self-esteem, self-concept and self-image during child development, through the influences of the environment and affective relationships between the people with whom the child lives. The study is a review of narrative literature, through publications/articles in the following databases: Scientific Electronic Library (SCIELO), Latin American and Caribbean Literature on Health Sciences (LILACS) and Virtual Health Library (BVS). Studies have shown the importance of developing a positive self-concept to have a good quality of life. For that, the relationships that the individual establishes in the family, in the school, in his social environment are fundamental for the formation of the self-concept.